Platinum(II) and Palladium(II) Complex Compounds as Anti-cancer Drugs. Methods of Cytotoxicity Determination - Pranczk, Joanna; Jacewicz, Dagmara; Wyrzykowski, Dariusz; Chmurzynski, Lech (Current Pharmaceutical Analysis, 2014)
The studies of new anti-cancer drugs are constantly in the centre of scientific interest. This paper provides an overview of the complex compounds of platinum(II) and palladium(II) as anti-cancer drugs. These drugs have been described in dependence on the type of cells which are under the influence of the cytotoxic drug and side effects arising from the use of the drug. In the case of some drugs such as cisplatin or trans-[PtCl2(tz)2] the mechanisms of action in the body are described. Furthermore, in the paper the methods used for cytotoxicity determination of chemical compounds considered to be used as anticancer drugs are described. The MTT, MTS, LDH, BrdU, Alamar Blue and Neutral Red test are examples of such methods.
Keywords: platinum(II) and palladium(II) complexes